2019
DOI: 10.3390/cells8121544
|View full text |Cite
|
Sign up to set email alerts
|

Platyconic Acid A, Platycodi Radix-Derived Saponin, Suppresses TGF-β1-Induced Activation of Hepatic Stellate Cells via Blocking SMAD and Activating the PPARγ Signaling Pathway

Abstract: Platycodi radix is a widely sold health food worldwide, which contains numerous phytochemicals that are beneficial to health. Previously, we reported that saponin from the roots of Platycodi radix-derived saponin inhibited toxicant-induced liver diseases. Nevertheless, the inhibitory effect of platyconic acid A (PA), the active component of Platycodi radix-derived saponin, on the anti-fibrotic activity involving the SMAD pathway remains unclear. We investigated the inhibitory effects of PA on TGF-β1-induced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Results of the present study demonstrated that PA exerted no effect on MRC-5 cell viability at concentrations of 0.5, 1.0 and 2.0 µM. A previous study reported that PA inhibits TGF-β1-induced proliferation of hepatic fibroblasts in a dose-dependent manner (33). The results of the present study demonstrated that TGF-β1 induction significantly increased proliferation of MRC-5 cells; however, PA treatment markedly inhibited the over-proliferation induced by TGF-β1.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Results of the present study demonstrated that PA exerted no effect on MRC-5 cell viability at concentrations of 0.5, 1.0 and 2.0 µM. A previous study reported that PA inhibits TGF-β1-induced proliferation of hepatic fibroblasts in a dose-dependent manner (33). The results of the present study demonstrated that TGF-β1 induction significantly increased proliferation of MRC-5 cells; however, PA treatment markedly inhibited the over-proliferation induced by TGF-β1.…”
Section: Discussioncontrasting
confidence: 55%
“…To date, only a small number of drugs have been approved for the treatment of pulmonary fibrosis-associated diseases, such as idiopathic pulmonary fibrosis (IPF), which exhibits a poor prognosis (31). The results of previous studies have demonstrated the role of PG in treatment of pulmonary disease and the anti-liver fibrotic effect of the active component PA (32,33). However, the specific mechanisms involved in the inhibitory effect of PA on pulmonary fibrosis are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Choi et al showed that PPAR-γ agonists could prevent TGF-β-induced fibrogenesis. They found that PPAR-γ is a new target in the treatment of liver fibrosis and inflammation 70 . A recent study also showed that administration of Lactobacillus amylovorus for 12 weeks reduced the adipocyte and plasma cholesterol levels and also increased the expression of hepatic and adipose PPAR -α 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase reporter assay was performed according to the literature published previously (J. H. Choi et al, 2019). Briefly, HACAT cells were seeded in 96-well plates and were incubated at 37 C overnight.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%